Structural and Elastic Characterization of Biopolymers Hydrolysis by Acoustic Microscopy. Issue 1 (15th February 2021) - Morokov, Egor; Demina, Varvara; Sedush, Nikita; Kalinin, Kirill; Dmitryakov, Petr; Krasheninnikov, Sergei; Khramtsova, Elena; Grigoriev, Timofei; Chvalun, Sergei; Levin, Vadim
Abstract: In this work, the high‐frequency acoustic microscopy is applied for imaging of internal microstructure and measurement of elastic characteristics of the biodegradable polymers based on D, L ‐lactide, L ‐lactide, ε‐caprolactone, and their copolymers. Acoustic microscopy results (images of microstructure in the volume and values of sound speed) have been supplemented by data on gel permeation chromatography, differential scanning calorimetry, and mechanical tensile test obtained on the polymers under the hydrolysis range from initial state to 8 weeks with step of 2 weeks. The features of ultrasound visualization and elastic characterization of each the polymer type have been discussed. The changes of the ultrasound characteristics have been detected in the high‐rate degradation polymers.